EFFICIENCY OF POLIVITAMIN COMPLEX ADMINISTRATION IN CHILDREN WITH ALLERGIC DISEASES - V.F. Lapshin; T.R. Umanets (Педиатрическая фармакология)
The article presents the results of clinical research to study the efficiency and portability of polivita-min complex in children with allergic diseases. Research found that inclusion in the complex treatment polivitamin complex studied in children allowed to raise the efficiency pathogenetic therapy helped correct the symptoms of hypo vitaminosis. A good test of the drug and no adverse reactions in children allowed to recommend it as the drug of choice in children with allergic diseases.Key words: children, allergic disease, vitamins and mineral complexes.